2021
DOI: 10.3389/fnmol.2021.709390
|View full text |Cite
|
Sign up to set email alerts
|

Junctophilins: Key Membrane Tethers in Muscles and Neurons

Abstract: Contacts between the endoplasmic reticulum (ER) and plasma membrane (PM) contain specialized tethering proteins that bind both ER and PM membranes. In excitable cells, ER–PM contacts play an important role in calcium signaling and transferring lipids. Junctophilins are a conserved family of ER–PM tethering proteins. They are predominantly expressed in muscles and neurons and known to simultaneously bind both ER- and PM-localized ion channels. Since their discovery two decades ago, functional studies using junc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…The T-tubule and sarcoplasmic reticulum (SR) membrane contact sites called dyad junctions, analogous to the vertebrate triad junctions, mediate local calcium dynamics for excitation-contraction coupling along sarcomeres (Peachey, 1968, Smith, 1966). As an indicator of the dyads, we detected Junctophilin (Jp), a conserved SR-anchored junction protein (Calpena et al, 2018, Piggott and Jin, 2021, Takeshima et al, 2000). In wildtype muscle, Jp localized as expected to uniformly-distributed foci associated with both SR and T-tubule membranes (marked by Rtnl1 and Dlg1, respectively; Figure 3A-3B; Supplemental Figure S3A ).…”
Section: Resultsmentioning
confidence: 99%
“…The T-tubule and sarcoplasmic reticulum (SR) membrane contact sites called dyad junctions, analogous to the vertebrate triad junctions, mediate local calcium dynamics for excitation-contraction coupling along sarcomeres (Peachey, 1968, Smith, 1966). As an indicator of the dyads, we detected Junctophilin (Jp), a conserved SR-anchored junction protein (Calpena et al, 2018, Piggott and Jin, 2021, Takeshima et al, 2000). In wildtype muscle, Jp localized as expected to uniformly-distributed foci associated with both SR and T-tubule membranes (marked by Rtnl1 and Dlg1, respectively; Figure 3A-3B; Supplemental Figure S3A ).…”
Section: Resultsmentioning
confidence: 99%
“…If CaV1 and RyR function in the same vesicle fusion pathway, they should be colocalized (Piggott & Jin, 2021). RyR was tagged with HALO at the N-terminus of the neuronal isoform (Extended Data Figure 4C) (Marques et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…These observations indicate that JPH2 is essential for the formation of CRUs in the heart, at both dyads and peripheral couplings. In addition to this tethering role, JPH2 also facilitates communication between RyR2 and Ca v 1.2 at these CRUs [86]. Recently, it was demonstrated that the joining region of JPH2 interacts directly with Ca v 1.2, recruiting the LTCC to the cardiac dyad [87].…”
Section: (B) Junctophilinsmentioning
confidence: 99%